Relationships Among Cognitive Function, Frailty, and Health Outcome in Community-Dwelling Older Adults - Xue, Huiping; Huang, Chunxia; Zhu, Qin; Zhou, Shuixin; Ji, Yunlan; Ding, Xiaohui; Zhang, Dandan; Gu, Dongmei (Frontiers in Aging Neuroscience, 2022)
Background: Frailty and cognitive impairment are significant problems faced by the elderly, which have a significant impact on their activities of daily living, social activities, and quality of life. Design: Cross-sectional study, Methods: 252 elderly people in two communities in Yangzhou were randomly selected. The cognitive function of the elderly was assessed using the Memory and Executive Screening (MES). The frailty phenotype was used to evaluate the elderly. The activity of daily living (ADL), functional activities questionnaire (FAQ), and European quality of 5-dimensions (EQ-5D) were used to evaluate health outcomes in the elderly. Results: The prevalence of mild cognitive impairment (MCI) among the elderly in the communities was 32.54%. There was a significant direct correlation between cognitive function and frailty; the direct effect was -0.521. The influence path of cognitive function on health outcomes included direct and indirect effects; the total effect was -0.759. The effect of frailty on health outcomes included direct and indirect effects; the total effect was 0.440. Conclusion: Cognitive function interacts with frailty and may reduce the quality of life, the ADL, and social activities among the elderly. In the future we can improve the health outcomes in the elderly directly or indirectly through the development of corresponding cognitive interventions and frailty prevention measures.